Az elérhetőség modellezési lehetőségei - Győrffy, Ildikó (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
It is well established - according to several literature and references in the topic of the regional development - that the quality standards of the transport networks are in a strong connection with the economic situation of an area. Through the availability potentials, the transport system can also have an effect on the intensification of the regional connections, therefore its development becomes an important purpose increasingly. In the study I described the availability position of the 174 Hungarian subregions. To streamline and enlarge the regional road infrastructure would be necessary to improve our competitive potentials and also to assist and increase the economic development processes. Their economic, social and institutional terms have to possess satisfactory internal and external connections.